Exploring The Potential of Diabetes Panel and Albumin as Predictors on Urinary Incontinence in Elderly - Yulfitra Soni; Nicholas Albert Tambunan; Alexander Halim Santoso; Bryan Anna Wijaya; Angel Sharon Suros; Bobby Marshel Ancheloti Waltoni (Universitas Muhammadiyah Manado, 2025)
Urinary incontinence (UI) is a significant health issue among the elderly, affecting their quality of life. While its etiology is multifaceted, metabolic and nutritional markers such as diabetes panel parameters and albumin levels may play a role in its severity. However, the relationship between these biomarkers and UI remains underexplored. This study aims to investigate the association of diabetes panel components and albumin levels with the severity of UI in elderly individuals to identify potential predictors. A cross-sectional analytic study was conducted involving 93 elderly participants from Bina Bhakti Nursing Home. UI was assessed using the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF). Metabolic markers were analysed using validated methods, including fasting glucose, HbA1c, fasting insulin, HOMA-IR, and albumin. Data were statistically analyzed using Spearman’s Rho and multiple regression analyses to determine correlations and predictive relationships. Significant correlations were observed between HbA1c (r = -0.284, p = 0.006) and albumin (r = -0.259, p = 0.012) with UI severity. Multiple regression analysis confirmed that HbA1c and albumin are significant predictors of UI, with lower levels associated with increased UI severity. Diabetes panel parameters, particularly HbA1c and albumin levels, are valuable predictors of UI severity in elderly individuals. These findings emphasize the importance of metabolic and nutritional health monitoring in managing and mitigating UI symptoms. Future longitudinal studies and intervention trials are recommended to validate these findings and explore therapeutic implications.